Effects of liraglutide on astrocyte polarization and neuroinflammation in db/db mice: focus on iron overload and oxidative stress - An, Ji-Ren; Liu, Jun-Tong; Gao, Xiao-Meng; Wang, Qing-Feng; Sun, Gui-Yan; Su, Jia-Nan; Zhang, Chi; Yu, Jia-Xiang; Yang, Yu-Feng; Shi, Yan (Frontiers in Cellular Neuroscience, 2023)
Neuroinflammation plays a crucial role in the occurrence and development of cognitive impairment in type 2 diabetes mellitus (T2DM), but the specific injury mechanism is not fully understood. Astrocyte polarization has attracted new attention and has been shown to be directly and indirectly involved in neuroinflammation. Liraglutide has been shown to have beneficial effects on neurons and astrocytes. However, the specific protection mechanism still needs to be clarified. In this study, we assessed the levels of neuroinflammation and A1/A2-responsive astrocytes in the hippocampus of db/db mice and examined their relationships with iron overload and oxidative stress. First, in db/db mice, liraglutide alleviated the disturbance of glucose and lipid metabolism, increased the postsynaptic density, regulated the expression of NeuN and BDNF, and partially restored impaired cognitive function. Second, liraglutide upregulated the expression of S100A10 and downregulated the expression of GFAP and C3, and decreased the secretion of IL-1β, IL-18 and TNF-α, which may confirm that it regulates the proliferation of reactive astrocytes and A1/A2 Phenotypes polarize and attenuate neuroinflammation. In addition, liraglutide reduced iron deposition in the hippocampus by reducing the expression of TfR1 and DMT1 and increasing the expression of FPN1; at the same time, liraglutide by up-regulating the levels of SOD, MDA, GSH and SOD2 expression, as well as downregulation of MDA levels and NOX2 and NOX4 expression to reduce oxidative stress and lipid peroxidation. The above may attenuate A1 astrocyte activation. This study preliminarily explored the effect of liraglutide on the activation of different astrocyte phenotypes and neuroinflammation in the hippocampus of a T2DM model and further revealed its intervention effect on cognitive impairment in diabetes. Focusing on the pathological consequences of astrocytes may have important implications for the treatment of diabetic cognitive impairment.